Sputum positivity status for acid fast bacilli in patient attending a designated microscopy centre of a tertiary care hospital, Lucknow - Raza, Adil; Jamali, Sana; Srivastava, V. K. (International Journal of Research in Medical Sciences, 2024)
Background: Tuberculosis is a contagious bacterial disease that is considered to be one of the deadliest diseases worldwide. It affects lungs and causes pulmonary TB. Today in India, every minute 3 to 4 people die of TB, more than 1000 die every day and more than 5 lakhs die every year. Demonstration of AFB in smear has a great important in control of TB, as smear positivity directly correlates with infectivity. Methods: It was a cross-sectional study. It lasted over a period of 6 months (January to June). Samples were collected from patients attending TB and Chest OPD of IIMS&R Hospital and sent for AFB examination by Ziehl-Neelsen (ZN) microscopy at microbiology lab. Patients with symptom of cough lasting for more than 2 weeks were included. Results: Out of 718 patient’s samples, 128 were smear positive by ZN staining method. Out of which 81 (63.28%) were males and 47 (36.72%) were females. According to age distribution 35 (27.35%) were <30 years of age, 68 (53.12%) were in between 30 and 60 while 25 (19.53%) were >60 years of age. 105 (82.03%) positive patients were found to be from rural area and remaining 23 (17.9%) patients belong to urban area. 29 patients were found to have a past history of TB of 1 year. Out of 128 positive patients none were smokers. 25 (19.53%) were tobacco chewers. 11 (8.56%) were contact with a case of TB. Conclusions: Demonstration of AFB in smear has a great important in control of TB, as smear positivity directly correlates with infectivity. Z-N staining method is the most commonly used worldwide.